Impact of Design on the Activity of ZrO2 Catalysts in Cellulose Hydrolysis-Dehydration to Glucose and 5-Hydroxymethylfurfural - Tatiana B. Medvedeva (MDPI AG, 2021)
The one-pot hydrolysis-dehydration of activated microcrystalline cellulose was studied in pure hydrothermal water at 453 K over ZrO2 catalysts produced by thermodegradation, microwave treatment, mechanical activation, and sol–gel methods and spent without any co-catalyst. ZrO2 prepared by microwave treatment was more active compared to ones derived by other methods. The catalyst calcination temperature also impacted reactivity. The cellulose conversion increased simultaneously with acidity and SBET, which in turn were set by the preparation method and calcination temperature. Phase composition did not affect the activity. Yields of glucose and 5-HMF reaching 18 and 15%, respectively, were over the most promising ZrO2 prepared by microwave treatment at 593 K. To our knowledge, this ZrO2 sample provided the highest activity in terms of TOF values (15.1 mmol g−1 h−1) compared to the pure ZrO2 systems reported elsewhere. High stability of ZrO2 derived by microwave irradiation was shown in five reaction runs.